2010
DOI: 10.1098/rspb.2010.1847
|View full text |Cite
|
Sign up to set email alerts
|

Vocal frequency change reflects different responses to anthropogenic noise in two suboscine tyrant flycatchers

Abstract: Anthropogenic noise is prevalent across the globe and can exclude birds from otherwise suitable habitat and negatively influence fitness; however, the mechanisms responsible for species' responses to noise are not always clear. One effect of noise is a reduction in effective acoustic communication through acoustic masking, yet some urban songbirds may compensate for masking by noise through altering their songs. Whether this vocal flexibility accounts for species persistence in noisy areas is unknown. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 31 publications
1
99
1
5
Order By: Relevance
“…Here, the fundamental question we consider is the effect of the noise treatment under normative conditions, and not variation in song features of exemplar songs. This strategy helps inform how changing acoustic conditions impact typical songs and may better generalize across species, because some species appear not to modify vocalizations in response to noise (Hu and Cardoso 2010, Francis et al 2011b, 2012b.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the fundamental question we consider is the effect of the noise treatment under normative conditions, and not variation in song features of exemplar songs. This strategy helps inform how changing acoustic conditions impact typical songs and may better generalize across species, because some species appear not to modify vocalizations in response to noise (Hu and Cardoso 2010, Francis et al 2011b, 2012b.…”
Section: Methodsmentioning
confidence: 99%
“…The wells are situated in surrounding woodlands whose vegetation structure remains similar irrespective of location or presence of compressors (Francis et al 2009, but see Francis et al 2012a). Given these conditions, experiments run in this system have the exceptional advantage of isolating the effects of chronic anthropogenic noise for use as a controlled treatment variable (Francis et al 2011b). This arrangement stands in contrast to many field systems where it is difficult to fully control for the confounding effects of urban environments.…”
Section: Introductionmentioning
confidence: 99%
“…Some ornithologists considering biophony-anthrophony interactions have conducted interesting studies, mostly examining impacts of anthropogenic noise. For example, several studies have demonstrated that birds can modify the frequency and amplitude of their signals, shift their daily temporal activity patterns, and move to different locations in the landscape to avoid the potential masking effects of anthropogenic sound (Brumm and Slabbekoorn 2005, Francis et al 2011, Dowling et al 2012). …”
Section: Principles Of Soundscape Ecology Related To Avian Ecology Ementioning
confidence: 99%
“…Although not all species appear capable of adjusting signals to changing environmental conditions [4], intraindividual song variability may be used to maximize signal transmission in variable environmental conditions, such as in response to seasonal changes or urban noise [5]. In contrast, intraspecific variation via adaptation to local conditions may be most common when species have large geographical ranges or if sexual selection is especially strong [8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, most studies have used acoustic traits (e.g. frequency, song length) averaged per population or species, but recent studies show that signal variation at the level of the individual can also be important for acoustic communication in a variety of environments [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%